Realizing controllable quantum states : (World Scientific, 2005)
This volume is a collection of papers from the third meeting of the international symposium on mesoscopic superconductivity and spintronics. Research on quantum information technology has advanced a great deal since the previous meeting. Mesoscopic physics, such as spins in nano-scale semiconductor structures, micro-fabricated superconducting junctions and extraordinary metal contacts have now been not only theoretically but also experimentally established as important solid-state elements of quantum information devices. The book also contains some papers on information theory from the viewpoint of quantum algorithms, indicating that further collaboration between physics and computer science promises to produce fruitful results in quantum information technology.